Evaluation of the Patient Comfort of Hemodialysis Access with Visual Analogue Scale - Acipayam, Mehmet; Altinay, Levent; Halici, Umit; HuseyinovSuat Canbaz, Serhat (Annals of Medical Research, 2021)
Aim: In this study, we investigated the effects of catheter application sites on patients’ quality of life and comfort.